2019
DOI: 10.1111/iwj.13113
|View full text |Cite
|
Sign up to set email alerts
|

A pilot feasibility randomised clinical trial comparing dialkylcarbamoylchloride‐coated dressings versus standard care for the primary prevention of surgical site infection

Abstract: A surgical site infection (SSI) may occur in up to 30% of procedures and results in significant morbidity and mortality. We aimed to assess the feasibility of conducting a randomised controlled trial (RCT) examining the use of dialkylcarbamoylchloride (DACC)-impregnated dressings, which bind bacteria at the wound bed, in the prevention of SSI in primarily closed incisional wounds. This pilot RCT recruited patients undergoing clean or clean-contaminated vascular surgery. Participants were randomised intraoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 45 publications
0
19
0
3
Order By: Relevance
“…The ASEPSIS scoring system was used to assess the wound between postoperative days 5 and 7 and at postoperative day 30 ± 3 days. For further details on data collection methods for the primary outcomes see Totty et al 11 During the study, data were also collected on a series of secondary outcomes, including antibiotic use, LOS, time taken to return to work, and readmission to hospital. At each study follow‐up time point, patient‐reported HRQoL was recorded using the EQ‐5D‐3L instrument 14…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ASEPSIS scoring system was used to assess the wound between postoperative days 5 and 7 and at postoperative day 30 ± 3 days. For further details on data collection methods for the primary outcomes see Totty et al 11 During the study, data were also collected on a series of secondary outcomes, including antibiotic use, LOS, time taken to return to work, and readmission to hospital. At each study follow‐up time point, patient‐reported HRQoL was recorded using the EQ‐5D‐3L instrument 14…”
Section: Methodsmentioning
confidence: 99%
“…These records were not excluded from the primary outcomes analysis which focused on the feasibility of conducting a full RCT 11 . A final total of 136 patients were available for this analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, an adverse effect of prophylactic CSD is that they may become a potential infection source and act as an infection path into the depths of the wound 9 . Some literature indicates that CSD plays an important role in the development of surgical site infection in orthopaedic trauma patients 10,11 . Besides this, according to a meta-analysis of the efficacy of CSD in orthopaedic patients, postoperative blood transfusion was required more frequently in those patients with drainage used 12 .…”
Section: Introductionmentioning
confidence: 99%